Use of hemoglobin (Hb) for iron deficiency anemia diagnosis - Gonzales, Gustavo F (2019)
Anemia is a worldwide public health problem that affects both the health and survival of people. It is estimated that 25% of the world population suffers it. Although most of the countries have been intervening during fifty years to reduce the rates of anemia, these efforts are unsatisfactory. Among the arguments used to explain this low success, is the low adherence to the consumption of iron supplements. The hepcidin discovery in 2000 has changed our knowledge about the mechanisms that regulate iron homeostasis, which shows that the inflammatory processes, which are responsible for 42% of anemia cases in the world will not respond to the intervention with oral iron, due to the increase in the value of hepcidin by inflammation. In this review it is also argued that the criteria used to determine the cut-off points in children and pregnant women to define iron deficiency anemia do not agree with the normality figures established in several countries in the world. Thus, the cut-off point of 11 g / dL of Hb defined to determine anemia in pregnant women and children is above the mean-two standard deviations of the populations evaluated. Evidence is also described that suggests that the correction of hemoglobin by altitude of residence would be unnecessary and erroneously increasing the prevalence of anemia in high-altitude populations. To sum up, the evidence suggests that adjusting hemoglobin for altitude is unnecessary, and significantly increases the prevalence of anemia in high altitude population. The Hb cut-off point 11 g / dL should be redefined to diagnose anemia in children under 60 months of age and in pregnant women. In a way to better define iron deficiency anemia, other biomarkers should be considered to evaluate the content of body iron, always adjusting for the inflammatory contribution. By these means we can accurately distinguish the prevalence of iron deficiency anemia, excluding the other types.